Dinamika Sosial dalam Praktik Pelaksanaan Upacara Pernikahan Adat Fangowai dan Fame’e Afo di Kecamatan Botomuzoi Kabupaten Nias - Leni Kristiani Lase; Martua Sihaloho; Jupalman Welly Simbolon; Sudirman Lase (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The Fangowai and Fame’e Afo traditions are important parts of Nias traditional wedding ceremonies, rich in symbolic and social values. However, modernization, time efficiency, and economic pressures have influenced their implementation. This study aims to describe the social dynamics in the implementation of Fangowai and Fame’e Afo in three villages in Botomuzoi District: Hiligodu, Ononamolo Talafu, and Lasara, with a focus on changes in the form of the procession, causal factors, and the transformation of symbolic meaning. The approach used is descriptive qualitative through observation and in-depth interviews with community leaders. customs, society, and youth, as well as field documentation. Data were analyzed through data reduction, presentation, and conclusion drawing, and their validity was tested through source triangulation. The results showed a simplification of the time and stages of the procession, a reduction in the number of traditional figures, and an adjustment of the number of sacrificial pigs to reflect economic capacity. Symbolic transformation also occurred with the addition of cigarettes to the Bola Nafo ceremony, but the meaning of betel as a symbol of respect and brotherhood was maintained. These changes reflect the adaptation of the Nias people to the modern social context without losing the core values of tradition.